2019
DOI: 10.1016/j.ekir.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine in Pregnancy: A Systematic Review

Abstract: Introduction Standard assessment of renal function in pregnancy is by measurement of serum creatinine concentration yet normal gestational ranges have not been established. The aim of this systematic review was to define the difference in serum creatinine in a healthy pregnancy compared with concentrations in nonpregnant women to facilitate identification of abnormal kidney function in pregnancy. Methods Medline, PubMed, Embase, Web of Science, theses, key obstetric tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 62 publications
8
58
2
2
Order By: Relevance
“…This may be an indication of renal involvement because serum creatinine has proven to be useful in the detection and assessment of acute kidney injury and chronic kidney disease. [10,11] The findings are similar to other reports which showed that creatinine levels were significantly higher in hypertensive subjects. [31,32] The study also recorded a positive significant correlation of urea and creatinine in hypertensive subjects and control.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be an indication of renal involvement because serum creatinine has proven to be useful in the detection and assessment of acute kidney injury and chronic kidney disease. [10,11] The findings are similar to other reports which showed that creatinine levels were significantly higher in hypertensive subjects. [31,32] The study also recorded a positive significant correlation of urea and creatinine in hypertensive subjects and control.…”
Section: Discussionsupporting
confidence: 91%
“…Serum creatinine is used in the detection and assessment of acute kidney injury and chronic kidney disease. [10,11] Creatinine is a by-product of energy metabolism that is filtered from the blood by kidneys and is excreted into the urine. [12] Creatinine is removed from the body entirely by the kidneys and if kidney function is abnormal, creatinine level will increase in the blood.…”
mentioning
confidence: 99%
“…Though there have been several studies that aimed at defining the reference values for serum creatinine, none are considered accurate in pregnancy [23,25,26]. A recent systematic review found that, using a nonpregnant reference interval of 45–90 mmol/L (0.51–1.02 mg/dL), a serum creatinine higher than 77 mmol/L (0.87 mg/dL) should be considered pathological, outside the normal range for pregnancy [23] (Table 1).…”
Section: Physiological Changes and Kidney Adaptation To Pregnancymentioning
confidence: 99%
“…The international consensus classifications mentioned above and illustrated in Table 3 and Table 4 are used for defining and staging AKI in non-pregnant patients and cannot be extrapolated to pregnancy. The rapid deterioration of kidney function that characterizes AKI has been variably defined in pregnancy, either as an increase in serum creatinine over 80 mg/dL, doubling in serum creatinine levels, oliguria of <400 mL/24 h or the need of dialysis [23,66,67]. The lack of consensus in PR-AKI definitions arises from the physiological variability in the cardiovascular haemodynamics and renal function changes in the pregnant population.…”
Section: Challenges In Diagnosis Of Pr-akimentioning
confidence: 99%
See 1 more Smart Citation